Caracterización agromorfológica de 30 accesiones de Phaseolus spp. desde la etapa fenológica de floración hasta maduración, en el cantón Salcedo provincia de Cotopaxi 2021 - Viteri Díaz, Doris Alicia (2021)
The research project was carried out in Anchiliví Neighborhood, Salcedo Canton with the objective of characterizing agronomically and morphologically 30 accessions of Phaseolus spp since the stage of flowering until maturation, accessions collected in different sectors of the country. The essay was implemented in five blocks, each 1.5 long by 16 rows at 0.80 m between rows, each row had a different accession and they were separated by a corn row to avoid the accessions crossing. 21 descriptors proposed by (IBPGR, 1982) and (Muñoz Giraldo & Jose, 1993) were evaluated. The variables evaluated gave the following results: floral button, 100% presented globular floral button, Wings color, 13 accessions (44%), presented lilac color and 17 accessions (56%) presented different color (White, purple, red), the banner color, (44%) of the accessions presented purple color (13 accessions) and the remaining (56%) presented different colors ( white, violet, red, scarlet), presence of the venations on the banner , 100% (30 accessions) presented venations; color of venations, 11 accessions (36%) presented green color with purple pigment in the veins . 7 accessions (23%) reddish brown and the 12 remaining (41%) presents different colors ( lilac, green with pink and purple pigments); color of the calix, 14 accessions (46%) presented green color, 6 accessions (20%) reddish brown, 8 accessions (27%) green with purple pigment and 2 purple (7%); keel color, 14 accessions (46%) presented white color with pure rib, 7 accessions (23%) pure white, 7 accessions (23%) scarlet red and 2 purple (7%); bracteole size , most of the accessions presented small bracteoles, shape of the bracteole, 50% ( 15 accessions ) presented ovate- acuminated bracteoles and 50% (15 accessions) almost round; stem growth habit, 22 accessions (73%) presented undetermined climbing growth habit , with load in the upper nodes ( Type IV); pod distribution on plants. 100% (30 accessions) presented uniform distribution, Plant height in P vulgaris in a period of 260 days is 185 to 292 cm P coccineus in the same period of 260 days is 240 to 280 cm P lunatus presented a height of 150 to 210 cm, P. dumosus presented in its study accession a height of 165 cm.